2-Bromo-5-tert-butyl-N-methyl-N-[2-(methylamino)phenyl]-3-(1-methyl-1H-benzimidazol-2-yl)benzamide - Prasad, Poonam Rajesh (International Union of Crystallography, 2014)
In the title compound, C(27)H(29)BrN(4)O, benzimidazole ring system and the amide moiety are planar [r.m.s. deviations = 0.016 (2) and 0.017 (1) Å, respectively]. The molecule adopts a conformation in which the amide linkage is almost perpendicular to the central ring [dihedral angle = 85.79 (8)°], while the benzimidazole ring system makes a dihedral angle of 70.26 (11)° with the central ring. In the crystal, the molecules form dimers through N—H⋯O hydrogen bonds and C—H⋯O interactions. These dimers are further linked into zigzag ribbons along [201] by weak C—H⋯Br interactions. As a result of the bulky nature of the molecule, as evidenced by the large dihedral angles between rings, there is little evidence for any π–π interactions.